Development of Carnivac-Cov vaccine against coronavirus infection (COVID-19) in carnivores - T. S. Galkina; A. A. Nesterov; A. V. Borisov; I. A. Chvala; A. V. Kononov (Ветеринария сегодня)
Development of specific protection in susceptible carnivores against COVID-19 caused by zoonotic agent is of great importance for maintaining epidemic and veterinary favourable situation in the Russian Federation and prevention of new coronavirus infection spread in humans. Development of inactivated adsorbed whole-virion vaccine (Carnivac-Cov) against coronavirus infection (COVID-19) for carnivores intended for specific disease prevention in fur animals and pet animals (cats and dogs) and tests of the vaccine for its safety and effectiveness are described in the paper. The vaccine was developed and tested at the FGBI “ARRIAH” (Vladimir) subordinated to the Rosselkhoznadzor in accordance with the Russian Federation legislation requirements. Clinical trials were carried out on fur farms, in veterinary clinics and animal shelters. More than 330 animals (fur animals, cats, dogs) were involved in the preclinical and clinical trials. The trials have demonstrated that the vaccine is safe for target animals. Carnivac-Cov vaccine administered twice intramuscularly at the dose of 1.0 cm3 induces anti-SARS-CoV-2 immune response 14 days after the second administration that lasts for at least 6 months. The vaccine transportation, storage and application do not require any specific protective equipment. The vaccine can be used on fur farms and in veterinary clinics without limitations. Carnivac-Cov is the first tool for specific COVID-19 prevention in animals. The vaccine has successfully passed comprehensive quality control and is registered in the Russian Federation.